2005
DOI: 10.1179/174329305x40714
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures of gas metal arc weld metal of 950 MPa class steel

Abstract: The effects of shielding gas composition on the properties and microstructure of single pass weld metals produced by GMA (gas metal arc) groove welding of 950 MPa class steel plates have been investigated. The shielding gas employed was a mixture of argon (Ar) and carbon dioxide (CO 2 ) (0-25%), and the weld heat input was ,3 kJ mm. With increasing CO 2 content, the hardness of the weld metal decreased from 380 HV to 280 HV, and the absorbed energy of the Charpy impact test decreased from 130 J to 90 J. The mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The results of the studies of Gouda et al [29] and Menzel [30] above are confirmed by Ebrahimnia et al [31], who examined the effect of shielding gas composition on the welding of steel ST 37-2 with GMAW. The following four different blends of shielding gas were tested: 97.5 % Ar + 2.5 % CO 2 , 90 % Ar + 10 % CO 2 , 82 % Ar + 18 % CO 2 and 75 % Ar + 25 % CO 2 .…”
Section: Effect Of Shielding On the Microstructuresupporting
confidence: 73%
See 2 more Smart Citations
“…The results of the studies of Gouda et al [29] and Menzel [30] above are confirmed by Ebrahimnia et al [31], who examined the effect of shielding gas composition on the welding of steel ST 37-2 with GMAW. The following four different blends of shielding gas were tested: 97.5 % Ar + 2.5 % CO 2 , 90 % Ar + 10 % CO 2 , 82 % Ar + 18 % CO 2 and 75 % Ar + 25 % CO 2 .…”
Section: Effect Of Shielding On the Microstructuresupporting
confidence: 73%
“…Gouda et al [29] found that shielding had noticeable effects on the microstructure of welded metal. Figure 11 shows the microstructure of the weld metal of 950 MPa class steel for different shielding gas mixtures.…”
Section: Effect Of Shielding On the Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…The control of weld metal microstructure as well as raising the welding productivity are critical factors for the development of weld metal of high-strength steel, to secure satisfactory mechanical properties and to reduce production costs [37].…”
Section: Mechanical and Microstructural Properties Of The Welded Jointmentioning
confidence: 99%
“…However, there is a relationship between the microstructure of welds and the shielding gas, because an increase in CO 2 contributes to a coarser microstructure with a higher volume fraction of nonmetallic inclusions, besides the growth in the burn rate of alloy elements of the base metal, such as silicon and manganese. Some works have reported changes on the mechanical properties due to the decrease of these alloying elements [37,[51][52][53]. Inclusions formed in the weld metal have two opposing effects on the impact toughness.…”
Section: Mechanical and Microstructural Properties Of The Welded Jointmentioning
confidence: 99%